A new treatment paradigm for trigeminal neuralgia using botulinum toxin type a. (5th August 2013) - Guardiani, Elizabeth; Sadoughi, Babak; Blitzer, Andrew; Sirois, David
<x xml:space="preserve">Abstract</x> Objectives To review the current data for the use of Botulinum toxin type A (BoNT‐A) in trigeminal neuralgia (TN) and to describe the preferred injection technique of BoNT‐A in TN. To propose a new treatment paradigm for TN incorporating the use BoNT‐A. Data Sources MEDLINE and Google Scholar databases. Review Methods The current data on BoNT‐A for TN were reviewed and analyzed for outcomes. Results Seven studies examining the use of BoNT‐A were identified: Two randomized double‐blind, placebo‐controlled studies and five prospective case series. All studies found BoNT‐A to be an effective treatment in the majority of patients; and the results of the two randomized double‐blind placebo‐controlled study showed significant benefit over placebo. The majority of studies used an intradermal or subcutaneous injection technique. The most common side effect was transient facial paresis. Conclusions BoNT‐A offers a safe, effective, local treatment for TN that is nonablative in nature. BoNT‐A should be considered in patients who have failed, become refractory to, or are unable to tolerate first‐line pharmacologic treatments. Level of Evidence N/A. Laryngoscope, 124:413–417, 2014